DOES AGE INFLUENCE AI-ENABLED MOBILE BANKING APP USAGE? ANALYZING COGNITIVE FACTORS AND SUSTAINED INTENTIONS - Amy, Yeo Chu-May; Chee, Lee Ee; Yan3, Ong Yu (Graduate Program of Universitas Tarumanagara, 2025)
This research investigates the impact of cognitive aspects and AI attributes on the continued adoption of AI-powered mobile banking applications in Malaysia. It examines the relatively recent incorporation of AI into Malaysian mobile banking and the extent to which age influences user intentions. A total of 398 participants were surveyed, with data analysis conducted using SPSS. The results indicate that factors such as perceived usefulness, ease of use, enjoyment, and intelligence significantly contribute to users' continued engagement with AI-enabled banking apps, with age playing a moderating role. However, perceived anthropomorphism did not have a statistically significant effect on user intention, nor did age significantly moderate the connection between perceived intelligence and continuance intention. The study’s findings aim to enhance AI-enabled banking applications, fostering a more user-friendly and satisfying experience across different age groups. These insights provide valuable direction for software developers and financial institutions aiming to optimize user satisfaction and engagement with AI-powered mobile banking systems.